Termination of Employment with the Reason of Workers Refusing Transfers As a Result of the Covid-19 Pandemic in the Case at PT. New Hope East Java - Markoni Markoni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Currently, many companies are laying off their workers because they refuse to transfer, especially because of the covid-19 pandemic. In the case at PT. New Hope East Java workers were terminated because they refused to transfer as a result of the covid-19 pandemic. Mutation is an order from the company to rotate work from one position to another equal position. Compensation given by the company to workers who were laid off because they refused to transfer as a result of the covid 19 pandemic in the case at PT. New Hope East Java has complied with Law No. 13 of 2003 concerning Manpower. Due to the inconsistency of the Transfer Order with the Manpower Act, it is null and void and invalid. Thus, the reason for Termination of Employment by PT. New Hope East Java is null and void and is not valid. Therefore, a worker or employee refusing a transfer cannot be used as a reason for Termination of Employment by the employer. The compensation received by workers is in accordance with the provisions of the Manpower Act which is subject to Article 164 paragraph 1 of the Manpower Law Number 13 of 2003. However, in the case at PT. New Hope East Java does not calculate the annual leave entitlement that has not been taken and has not yet fallen for workers. Thus, workers are entitled to compensation of Rp. 72,397,560 (seventy-two million three hundred ninety-seven five hundred and sixty rupiah).